Ionic-liquid-assisted one-pot synthesis of Cu2O nanoparticles/multi-walled carbon nanotube nanocomposite for high-performance asymmetric supercapacitors. Issue 36 (1st June 2018) - Lu, Ying; Xu, Jian-Long; Ren, Shan; Zhong, Ya-Nan; Gao, Xu; Wang, Sui-Dong
Abstract : A one-pot room-temperature-ionic-liquid-assisted sputtering approach is designed to synthesize Cu2 O/MWCNTs nanocomposite with high capacitance and long cycling life due to synergistic effects of oxygen-deficient Cu2 O and conductive MWCNTs. Abstract : Finding earth-abundant and high-performance electrode materials for supercapacitors is a demanding challenge in the energy storage field. Cuprous oxide (Cu2 O) has attracted increasing attention due to its theoretically high specific capacitance, however, the development of Cu2 O-based electrodes with superior capacitive performance is still challenging. We herein report a simple and effective ionic-liquid-assisted sputtering approach to synthesizing the Cu2 O nanoparticles/multi-walled carbon nanotubes (Cu2 O/MWCNTs) nanocomposite for high-performance asymmetric supercapacitors. The Cu2 O/MWCNTs nanocomposite delivers a high specific capacitance of 357 F g −1, good rate capability and excellent capacitance retention of about 89% after 20 000 cycles at a current density of 10 A g −1 . The high performance is attributed to the uniform dispersion of small-sized Cu2 O nanoparticles on conductive MWCNTs, which offers plenty of redox active sites and thus improve the electron transfer efficiency. Oxygen vacancies are further introduced into Cu2 O by the NaBH4 treatment, providing the oxygen-deficient Cu2 O/MWCNTs (r-Cu2 O/MWCNTs) nanocomposite with significantly improved specific capacitance (790 F g −1 ) and cycling stability (∼93% after 20 000 cycles). The assembled asymmetric supercapacitor based on the r-Cu2 O/MWCNTs//activated carbon (AC) structure achieves a high energy density of 64.2 W h kg −1 at 825.3 W kg −1, and long cycling life. This work may form a foundation for the development of both high capacity and high energy density supercapacitors by showcasing the great potential of earth-abundant Cu-based electrode materials.